2011
DOI: 10.1021/ja2058567
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic Aryl Fluorination and Aryl Halide Exchange Mediated by a CuI/CuIII Catalytic Cycle

Abstract: Copper-catalyzed halide exchange reactions under very mild reaction conditions are described for the first time using a family of model aryl halide substrates. All combinations of halide exchange (I, Br, Cl, F) are observed using catalytic amounts of Cu(I). Strikingly, quantitative fluorination of aryl-X substrates is also achieved catalytically at room temperature, using common F(-) sources, via the intermediacy of aryl-Cu(III)-X species. Experimental and computational data support a redox Cu(I)/Cu(III) catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
144
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(160 citation statements)
references
References 44 publications
6
144
1
2
Order By: Relevance
“…Reaction yields were obtained by integration of the 1 H-NMR spectra of the crude reaction mixtures relative to the internal standard. The characterization of the halogenation products (L 1 -Cl, L 1 -Br and L 1 -I) has been achieved by direct comparison with authentic samples synthesized independently 18,39 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reaction yields were obtained by integration of the 1 H-NMR spectra of the crude reaction mixtures relative to the internal standard. The characterization of the halogenation products (L 1 -Cl, L 1 -Br and L 1 -I) has been achieved by direct comparison with authentic samples synthesized independently 18,39 .…”
Section: Methodsmentioning
confidence: 99%
“…and found that the corresponding L 1 -X coupling products were obtained quantitatively ( [37][38][39] . DFT calculations show that the reductive elimination of L 5 -Ag(III) is strongly exergonic (DG ¼ À 25.8 kcal Á mol À 1 ) and has a very low barrier (DG a ¼ 8.6 kcal Á mol À 1 ; for computed reaction profile see Supplementary Fig.…”
Section: Article Nature Communications | Doi: 101038/ncomms5373mentioning
confidence: 99%
“…The viability of an oxidative addition/reductive elimination sequence for fluorination of aryl halides via a Cu(I)/Cu(III) cycle was established by the Ribas group, using a designed macrocyclic substrate that allowed for isolation of key Cu(III) intermediates (Fig. 54) [111]. Halide exchange took place at an arylcopper(III) halide complex, followed by C-F reductive elimination from Cu(III).…”
Section: Nucleophilic Arene Fluorinationmentioning
confidence: 99%
“…While most of the evidence collected so far has shown that the active catalyst is a ligand-copper(I)-nucleophile [(L)Cu I (Nu)] species, there is no such agreement on the way this catalyst activates the aryl halide (ArY, Y = Cl, Br and I). The most invoked routes are based on either one-electron redox processes through the radical intermediate Cu I /Cu II catalytic cycle namely Single Electron Transfer (SET) and Halogen Atom Transfer (HAT) [4,[39][40][41][42], or on two-electron redox processes via a Cu I /Cu III catalytic cycle like Oxidative Addition-Reductive Elimination (OA-RE) or σ-bond Metathesis (MET) (Scheme 1) [37,38,[43][44][45][46][47][48][49][50]. Scheme 1.…”
Section: Introductionmentioning
confidence: 99%